Rancang Bangun Sistem Informasi Manajemen Perpustakaan Berbasis Web pada SMP Negeri Wimro: Rancang Bangun Sistem Informasi Manajemen Perpustakaan Berbasis Web pada SMP Negeri Wimro - Nur Arlin Hidayah; Josua Josen A. Limbong (JISTECH: Journal of Information Science and Technology, 2026)
The library is one of the school facilities that supports learning activities for students and teachers. Library collections, especially textbooks and reading materials, are used as references in the learning process. However, library management at SMP Negeri Wimro is still carried out manually using record books. This condition causes book data management, member data management, borrowing, returning, and report preparation to take a long time and be prone to recording errors. This study aims to design and develop a web-based library management information system to support library administration more effectively and efficiently. The system development method used in this study is the Waterfall method, consisting of requirements analysis, system design, implementation, testing, and maintenance. The system was developed using HTML, CSS, JavaScript, Node.js, Express.js, and MySQL. The results of this study are a web-based library management information system with features including user login, book data management, member data management, borrowing, returning, overdue fine calculation, lost book management, borrowing rules, report generation, and borrowing statistics charts. The testing results using the Black Box Testing method show that the main system features run according to their designed functions and can support library data management in a faster, more accurate, and structured manner.